Predisposing Factors, Pathologies, and Precipitating Factors Causing Intracerebral Hemorrhage - Alice Hosking; Neshika Samarasekera; Tom J. Moullaali; William N. Whiteley; Vega Pratiwi Putri; Mark A. Rodrigues; Colin Smith; Santosh B. Murthy; David Gaist; MUÑOZ VENTURELLI, PAULA ANDREA; Xin Cheng; Craig S. Anderson; et al. (Ovid Technologies (Wolters Kluwer Health), 2026)
Most people with spontaneous intracerebral hemorrhage (ICH) have hypertension, which is the strongest modifiable predisposing (risk) factor. However, multiple long-term medical conditions and other known predisposing factors for ICH usually coexist with hypertension, indicating that the causal pathway is multifactorial, and the term hypertensive ICH is oversimplistic. In this review, we integrate the highest quality evidence and our clinical experience in a framework to attribute multiple predisposing factors, underlying pathologies, and precipitating factors as the cause of ICH. In clinical practice, this framework supports physicians to take a holistic approach to treatment and prevention of ICH. In research, this framework shows how existing classification systems for the cause of ICH include underlying macrovascular, microvascular, and other structural pathologies but few predisposing or precipitating factors. Furthermore, this framework can inform the development of a more holistic classification system and expose knowledge gaps, including how predisposing factors lead to underlying pathologies and why only some people with these pathologies experience ICH.